SnO2 nanoparticles with controlled carbon nanocoating as high-capacity anode materials for lithium-ion batteries - Jayaprakash, N. (2012)
We demonstrate a facile route for the scalable synthesis of SnO2 nanoparticles with controlled carbon nanocoating for use as high-capacity anode materials for next-generation lithium-ion batteries. SnO2 nanoparticles with size in the range of 6 −10 nm are produced via a simple hydrothermal method with high yield, which are then encapsulated by a carbon layer through a modified method. The weight fraction of carbon present in the final product can be readily tuned by varying the concentration of glucose used during the hydrothermal coating process. A systematic study has been carried out to examine the effect of carbon content upon lithium-ion battery performance. It is found that the optimized SnO2@carbon nanoparticles manifest excellent lithium storage properties. As an example, SnO2@carbon with 8 wt % carbon can deliver a capacity as high as 631 mA h g^−1 even after 100 charge/discharge cycles at a current drain of 400 mA g^−1.